Adverse events in paediatric patients taken to magnetic resonance imaging under sedation or anaesthesia☆. Issue 1 (January 2017) - Largo‐Pineda, Carlos Eriel; Arenas‐Correa, Iván Darío; Ángel‐González, Gabriel Jaime; Vélez‐Arango, Jorge Mario; Calvo‐Betancur, Victor Daniel; Arango‐Zapata, Andrés Nahúm
ABSTRACT : Introduction: : Nuclear magnetic resonance is a technique requiring breath holding or staying still for long periods of time for image acquisition. For this reason, paediatric patients need to be given sedation or anaesthesia, creating additional risks to those found in other areas. Objective: : To describe the incidence of adverse events in paediatric patients in the magnetic resonance service with the presence of an anaesthetist. Materials and methods: : Descriptive observational study to assess the incidence of adverse events in 4786 patients under 15 years of age taken to magnetic resonance imaging with an attending anaesthetist for sedation or anaesthesia at Instituto de Alta Tecnología Médica between 2010 and 2014. Results: : There were 12 adverse events with a rate of 2.5 for every 1000 paediatric patients. Of these, there were 6 serious, 4 moderate and 2 mild adverse events. The proportion of mortality was 0.04%. Conclusion: : Performing magnetic resonance imaging studies under sedation or anaesthesia given by an anaesthetist in patients under 15 years of age is safe. However a risk‐benefit analysis is required in hospitalized or decompensated patients, in order to assess the best option. Eventos adversos en pacientes pediátricos sometidos a resonancia magnética bajo sedación o anestesia: RESUMEN: Introducción: : La resonancia magnética es una técnica donde se requieren apneas o periodos de inmovilidad considerables para la adquisición de imágenes. Inmovilidad que por condiciones de los pacientes pediátricos son difíciles mantener, requiriendo administración de sedación o anestesia generando riesgos adicionales a los existentes en otras áreas. Objetivo: : Describir la incidencia de eventos adversos en pacientes pediátricos en el servicio de resonancia magnética bajo asistencia por anestesiólogo. Materiales y métodos: : Estudio observacional descriptivo, donde se valoró la incidencia de eventos adversos en 4786 pacientes menores de 15 años que fueron llevados a resonancia bajo asistencia por anestesiólogo para sedación o anestesia en el Instituto de Alta Tecnología Médica entre los años 2010–2014. Resultados: : Se presentaron 12 eventos adversos, con un índice de 2.5 por cada 1000 pacientes pediátricos, de los cuales 6 eventos adversos fueron graves, 4 moderados y 2 leves. La proporción de mortalidad fue del 0.04%. Conclusión: : Realizar estudios de resonancia magnética bajo sedación o anestesia por anestesiólogo en pacientes menores de 15 años es seguro, sin embargo en pacientes hospitalizados o descompensados debe hacerse un análisis riesgo ‐ beneficio y valorar la mejor opción.